Strategi Pemasaran Produk Makanan Catering Melalui Media Sosial Instagram - Wayan Budi Mahardhika; Ni Nyoman Sunariani (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTThis study examines how marketing strategies are carried out by Catering businesses in Denpasar Bali. The use of social media as effective marketing is also felt and tried by all businesses, ranging from food, clothing and banking businesses. The use of social media is based on the rapid development of smart devices in which utilization is already very common and well known with everyone. Marketing strategies through social media like Instagram are also very often heard, especially people who are still productive. There are many examples of the use of social media to promote a product. With only a digital smart device and internet data package, everyone can access and also market their merchandise there. Instagram is very good to use because it relies on images as the main attraction, it is also equipped with the facilities to write comments and also short direct messages making Instagram a favorite in social media, especially for young people. The catering business also want to use Instagram. As this research was made, the four catering respondents selected based on the more than 1000 of followers are: Chika Catering, Catering Kerti Catering, Warung Umi Catering and Tunjung Asri Catering, have positive answer with the presence of this Instagram. Discussions using Marketing Mix show positive results in using Instagram to market their products.